(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
One of the leading and preventable causes of death in developing world is trauma and is a significant health and social issue. Impact of the trauma is dependent on site and severity of the force and the position of the victim when injured determine which set of organs is affected. only few cases were as a result of assault. In hospital deaths, maximum patients died within 6 hours of hospitalisation. Analysis of all the thoracic injuries showed the commonest injuries were rib injuries followed by trauma to the lungs. Liver was the commonest organ to get injured in abdominal trauma followed by pelvic fracture.